Hakikat Perkembangan Bahasa Anak Usia Sekolah Dasar: Sebuah Kajian Teoritis: Hakikat Perkembangan Bahasa Anak Usia Sekolah Dasar: Sebuah Kajian Teoritis - Maharani febriani; Widya Oktaviani Naibaho; Silvina Noviyanti; Selly Nurazizah (STKIP Subang, 2025)
Language development in elementary school-aged children is a gradual process closely linked to cognitive and social development. This study uses a literature review approach to examine various theories and research findings related to language development in elementary students. According to Jean Piaget's theory, children's language abilities improve along with cognitive maturation through specific developmental stages. During elementary school years, there is a significant increase in vocabulary acquisition and more complex grammatical structures, along with enhanced communication skills and active participation in discussions. Environmental factors, especially stimulation from social interactions with adults and peers, play a crucial role in accelerating language development. A deep understanding of the nature of children's language development is essential to support educational success and holistic personal growth. This study provides a theoretical foundation for developing language learning approaches tailored to individual children's needs. Keywords: language development, elementary school children, Piaget's theory, vocabulary, social interaction